2018
DOI: 10.5812/compreped.66245
|View full text |Cite
|
Sign up to set email alerts
|

Design, Validity and Reliability of the Cancer-Related Fatigue Questionnaire in Children with Cancer Aged 4 - 18 Years

Abstract: Background: Children and adolescents with cancer experience some complications such as pain, depression, and fatigue that impact the quality of life. Fatigue is one of the most common cancer treatment problems in most children with cancer. Objectives: The purpose of this study was to construct a comprehensive instrument to examine fatigue in patients with cancer (4-18 years). Methods: This descriptive study was conducted on 101 children with cancer. A questionnaire was designed to examine fatigue in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…In medical science, researchers use Cronbach's alpha coefficient for measuring the reliability of scales. If Cronbach's alpha is close to one, it shows that the internal consistency between questions is greater; and questions have high homogeneity (18). In this study, Cronbach's alpha was close to one for all dimensions of the questionnaire.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In medical science, researchers use Cronbach's alpha coefficient for measuring the reliability of scales. If Cronbach's alpha is close to one, it shows that the internal consistency between questions is greater; and questions have high homogeneity (18). In this study, Cronbach's alpha was close to one for all dimensions of the questionnaire.…”
Section: Discussionsupporting
confidence: 51%
“…In other words, in this way, the same questionnaire is completed by the same people at different times. Then, the correlation between the result is examined and the consistency of the questionnaire is evaluated using the inter-class correlation coefficient (ICC) (18). The results showed that ICC obtained in this study was close to one for all dimensions.…”
Section: Discussionmentioning
confidence: 85%
“…The Greek version can be downloaded at https ://www.koos.nu/. The sample is considered representative of children presenting a variety of knee disorders seen across this age range and their KOOS-Child baseline scores resemble baseline scores of relevant studies [14,24]. KOOS psychometric properties were considered satisfactory and were assessed up to 3 months post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If the Cronbach Alpha is close to one, it indicates the internal consistency between questions. 26 The results of this study showed that Cronbach's alpha was close to one. This indicated that consistency of the questionnaire was appropriate.…”
Section: Discussionmentioning
confidence: 53%
“…If the results of the distribution of the questionnaire in two periods were significantly correlated, it indicated high repeatability for the questionnaire. 26 The result of this study indicated that ICC for all dimensions was close to one. So if this questionnaire is used at different times on the same people, the same results will be achieved.…”
Section: Discussionmentioning
confidence: 55%